Nautical Depth Sounding- The Rheocable Survey Method - Druyts, Marc; Brabers, Peteralv (The International Hydrographic Review, 2012)
Since 1984, research and development activities have been undertaken in Belgium comprising in situ measurements and sea trials with TSHD ‘Vlaanderen 18’ in Zeebrugge. Towing tank experiments and sludge test tank experiments have also been performed in the laboratories of the Flanders Hydraulic Research. This work has enabled the authors to conclude that mud on the seabed consists of two different physical states occurring in the same configuration - fluid mud on top of solid (consolidating) mud. Fluid mud is navigable, solid mud is not. The interface between both is characterized by a drastic increase of rheological parameters, in particular, the yield stress. However, for the time being, this phenomenon cannot be fully interpreted scientifically. The Rheocable sounding method is designed to detect the interface between fluid and solid mud. A towed object, when kept in a velocity window, is always positioned at this interface between fluid and solid mud. This method makes it possible to develop a new maintenance dredging strategy - leave/ignore the fluid mud and remove only the solid mud. The dredging of fluid mud is therefore unnecessary – it is navigable (!) – and extremely uneconomical. Solid mud on the other hand is not navigable, is immobile and will absolutely maintain its position on the seabed unless removed by dredging action. Furthermore, the deployment of the Rheocable implies many operational and contractual advantages, including transparency of dredged quantities etc. The Rehocable cable sounding method allows for a considerably improved focus, smaller quantities and easier planning of the maintenance dredging activities, resulting in lower budgets and improved safety for shipping traffic.